THE IMPLEMENTATION OF THE FREE LEARNING CURRICULUM IN THE AQIDAH AKHLAK (FAITH AND MORALITY) STUDY FIELD - Ahmad Fauzi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to analyze and document the implementation of the Independent Curriculum in the field of Aqidah Akhlaq studies at Madrasah Aliyah Zainul Hasan 2 Mojolegi Gading. The research method involves observation, interviews, and documentation analysis to evaluate the effectiveness of the curriculum in forming students' religious and moral understanding. It is hoped that the results of this research can contribute to the development of religious curricula in similar institution